The Role of entrepreneurial strategies in achieving organizational excellence (American Journal of Business Management, Economics and Banking, 2022)
The research mainly aims to know the role of entrepreneurial strategies with its sub-dimensions in achieving organizational excellence, and the research was applied to a sample of (52) individuals that included directors of scientific departments and rapporteurs in the faculties of the University of Misan. The research is a set of statistical methods for analyzing, interpreting and processing data through the statistical package (SPSS V.24), and the research started from a major problem that states (What is the role of applying entrepreneurial strategies in achieving organizational excellence), and the research reached a set of conclusions, the most prominent of which were (with The surveyed sample has absolute confidence that the application of entrepreneurial strategies allows the exploitation of all critical opportunities using effective strategic planning that depends on a common organizational vision and the adequacy of available resources, by increasing the orientation towards a strategy of creativity, and facilitating the processes of readiness for initiative and aggressive competition), and in light of the conclusions, a set of The most important recommendations were (that the university is considered to be organizationally distinct, the senior management must make deliberate efforts to Engaging employees with leadership competencies and skills in order to support the vision of quality and service delivery).